1978
DOI: 10.1099/00207713-28-2-269
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic Acid Relatedness of Proteus and Providencia Species

Abstract: Deoxyribonucleic acid reassociation was used to determine relatedness among protei and providenciae and between these organisms and other members of the family Entero bacteriaceae. Ewing described four biogroups in Prov. alcalifaciens and two biogroups in Prov. stuartii. These are based on the production of gas from glucose and the fermentation of adonitol and inositol (17; see Table 12).Several other taxonomic proposals for Proteus and Providencia have been reviewed by Rauss (38). The best known of these is K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 8 publications
8
84
0
Order By: Relevance
“…However, these strains, which included several null alleles, were distinguished from other species by other esterases (Goullet & Picard, 1985). The esterase data for Providencia were in agreement with the genetic divergence measured by DNA reassociation studies (Brenner et al, 1978). Group 6.…”
Section: Multivariate Statistical Analysis Of the Six Groups Of Speciessupporting
confidence: 79%
“…However, these strains, which included several null alleles, were distinguished from other species by other esterases (Goullet & Picard, 1985). The esterase data for Providencia were in agreement with the genetic divergence measured by DNA reassociation studies (Brenner et al, 1978). Group 6.…”
Section: Multivariate Statistical Analysis Of the Six Groups Of Speciessupporting
confidence: 79%
“…The DNA-DNA hybridization study revealed that the strain C1112 T showed DNA-DNA similarities of 100, 48.1, 42.3, 22.6, 38.7, 39.1, 36.6, 19 (Brenner et al, 1978;Hickman-Brenner et al, 1983;Juneja and Lazzaro, 2009;Muller et al, 1986;Somvanshi et al, 2006). In addition, the results from the DNA-DNA hybridizations fall well below the 70% reassociation threshold recommendation of Wayne et al (1987) for designation of a novel species.…”
Section: Dna-dna Hybridization and Dna Base Compositionmentioning
confidence: 91%
“…morgani) ( I -5%) (Senior, 1979). DNA hybridisation studies (Brenner et al, 1978), urease isoenzyme profiles (Senior et al, 1980) and the sharing of phage (Coetzee, 1963) and bacteriocin receptors…”
Section: Introductionmentioning
confidence: 99%